How to apply responsible leadership theory in practice: A competency tool to collaborate on the sustainable development goals. (28th May 2020) - Muff, Katrin; Liechti, Anna; Dyllick, Thomas
Abstract: In the era of the sustainable development goals (SDGs) and calls for climate action, business is challenged to respond more effectively to societal and environmental challenges. Collaboration with stakeholders requires an ability for broader collaboration competencies. These form a part of an established literature on responsible leadership (RL) competencies. Human resources managers, consultants and educators in charge of developing such competencies demand clarity on the definition and a practical measurement tool for RL. This paper addresses both by proposing a RL definition and a RL competency model, that has been operationalized into a free online tool for individuals and groups. This free Competency Assessment for Responsible Leadership (CARL) tool is used to assess stakeholder engagement, individual and group leadership development, and internal sustainable development transformation work. The CARL online tool serves to systematically analyze and develop RL competencies, both in business and educational practices, and helps advance the RL theory based on insights from practice.